2017
DOI: 10.4097/kjae.2017.70.6.612
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between ketorolac and nefopam as adjuvant analgesics for postoperative patient-controlled analgesia: a randomized, double-blind, prospective study

Abstract: BackgroundWe compared the analgesic efficacy and side effects of ketorolac and nefopam that were co-administered with fentanyl via intravenous patient-controlled analgesia.MethodsOne hundred and sixty patients scheduled for laparoscopic cholecystectomy were randomly assigned to ketorolac (Group K) or nefopam (Group N) groups. The anesthetic regimen was standardized for all patients. The analgesic solution contained fentanyl 600 µg and ketorolac 180 mg in Group K, and fentanyl 600 µg and nefopam 120 mg in Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
(29 reference statements)
1
18
0
Order By: Relevance
“…Although a large number of clinical trials have explored the use of nefopam in various surgical settings,[ 9 ] the efficacy of nefopam in PCA remains unclear. [ 17 ] Only a few studies have reported the efficacy and side effects of using nefopam combined with fentanyl in PCA,[ 13 15 , 27 ] as in the present study. Kim et al compared three PCA groups after cardiac surgery: nefopam alone, fentanyl alone, or nefopam and fentanyl.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although a large number of clinical trials have explored the use of nefopam in various surgical settings,[ 9 ] the efficacy of nefopam in PCA remains unclear. [ 17 ] Only a few studies have reported the efficacy and side effects of using nefopam combined with fentanyl in PCA,[ 13 15 , 27 ] as in the present study. Kim et al compared three PCA groups after cardiac surgery: nefopam alone, fentanyl alone, or nefopam and fentanyl.…”
Section: Discussionmentioning
confidence: 75%
“…[ 25 , 26 ] However, the incidence of PONV was often not reduced by opioid-sparing strategies with nefopam, as reported in several randomized trials. [ 1 , 13 , 14 ] Furthermore, a few studies have even showed a relatively frequent PONV incidence in patients treated with nefopam,[ 12 , 27 ] suggesting that nefopam is emetic. A previous systematic review showed nefopam was not significantly associated with PONV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PCA cocktails often include either oxycodone or hydromorphone, both of which have a relatively long onset and duration of action. Most cocktails also include nefopam, which has a mechanism of analgesia that is different from that of opioids; the use of this agent helps reduce the dose of required opioids, which in turn reduces opioid-related side effects (Son et al 2017;Aveline et al 2009). To further reduce the opioid-induced side effects of nausea and vomiting, antiemetic drugs can be added to IV PCA (Estan-Cerezo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ketorolac is an NSAID with potent analgesic, antiinflammatory, and antipyretic properties, which can be used for painful sickle cell crisis. Studies demonstrated that ketorolac is comparable with morphine in relieving pain (19,20). Wright et al (21), Ender et al (14), Jacob and Mueller (22), Perlin et al (23), and Udeza and Herrera (6) reported that anti-inflammatory agents such as ketorolac do well in treating pain crisis in SCD patients.…”
Section: Discussionmentioning
confidence: 99%